Reliability and validity of kinetic and kinematic parameters determined with force plates embedded under a soil-filled baseball mound - Yanai, T.; Matsuo, A.; Maeda, A.; Nakamoto, H.; Mizutani, M.; Kanehisa, H.; Fukunaga, T. (Journal of Applied Biomechanics, 2017)
We developed a force measurement system in a soil-filled mound for measuring ground reaction forces (GRFs) acting on baseball pitchers and examined the reliability and validity of kinetic and kinematic parameters determined from the GRFs. Three soil-filled trays of dimensions that satisfied the official baseball rules were fixed onto 3 force platforms. Eight collegiate pitchers wearing baseball shoes with metal cleats were asked to throw 5 fastballs with maximum effort from the mound toward a catcher. The reliability of each parameter was determined for each subject as the coefficient of variation across the 5 pitches. The validity of the measurements was tested by comparing the outcomes either with the true values or the corresponding values computed from a motion capture system. The coefficients of variation in the repeated measurements of the peak forces ranged from 0.00 to 0.17, and were smaller for the pivot foot than the stride foot. The mean absolute errors in the impulses determined over the entire duration of pitching motion were 5.3 N?s, 1.9 N?s, and 8.2 N?s for the X-, Y-, and Z-directions, respectively. These results suggest that the present method is reliable and valid for determining selected kinetic and kinematic parameters for analyzing pitching performance.